(untitled) (Journal of Engineering, 2005)
A new design concept for a percolator is developed which combine the simultaneous production of ammonia vapor plus the pumping of weak aqua ammonia liquid. The steady state desig was based on a balance between the hydrostatic driving head and the total single and two-phase pressure losses in the percolator system. To accomplish this, the results from modeling of the driving pressure and pressure losses, using the separated flow and drift flux methods were compared with the experimental measurements. The Chisholm’s model was the best in predicting the measured flow rate versus water level for first stage with a maximum standard deviation of ± 10.1% and was adopted for the theoretical calculations. Parametric design studies that include the cooling power and the strong solution level, inner tube diameter and height for each stage of the percolator were carried out to maximize suitable cost function. The results of the optimization gave a two stage percolator of length 280 mm, inner diameter 5.5 mm for first stage and length 520 mm, inner diameter 5.5 mm for second stage.